Idiopathic retroperitoneal fibrosis with endometrial cancer: a case report and literature review - Manfei Si; Kun Zhang; Jiaxin Li; Huiying He; Ying Yao; Jinsong Han; Jie Qiao (BMC, 2022)
Abstract Background Retroperitoneal fibrosis is a rare disease characterized by chronic nonspecific inflammation, which leads to clinical compression manifestations of retroperitoneal organs especially ureter. Approximately 70 percent of retroperitoneal fibrosis cases are idiopathic which has no clear etiology. This study reported a rare case of a 48-year-old woman presented with idiopathic retroperitoneal fibrosis and endometrial cancer. Case presentation A 48-year-old woman presented with irregular vaginal bleeding without abdominal pain, bloating or discomfort. The patient was diagnosed iRPF after splenectomy 13 years ago. Then she took prednisone for 2 years and took tamoxifen for about 11 years. She stopped taking the medication from October 2019 to May 2020 and then started taking tamoxifen again until November 2020. Two weeks after she stopped taking tamoxifen, she presented with irregular vaginal bleeding. Gynecological ultrasound revealed a thick endometrium with uneven echo enhancement and blood flow signals. Then diagnostic curettage was performed with pathological examination showed endometroid carcinoma. Later, the patient was admitted to Peking University Third Hospital for surgery. Preoperative imaging examinations, including CT, MRI, and PET/CT, all showed pelvic enlarged lymph nodes and they were highly suspected to have lymph node metastasis. The patient underwent laparoscopic surgical staging and enlarged lymph nodes in the pelvic and aortic regions were removed. Finally, the pathology confirmed that endometrioid adenocarcinoma and fibrosis, but there was no tumor infiltration in these enlarged lymph nodes. The patient is now in good condition. Conclusion This case report stressed the difficulty to distinguish between lymph node metastasis and inflammatory hyperplasia by common imaging methods. Due to increased surgical difficulty among retroperitoneal patients, lymphadenectomy should be carefully evaluated to avoid additional surgical complications and over-treatment.